Phosphahelicenes in Asymmetric Organocatalysis: [3+2] Cyclizations of γ‐Substituted Allenes and Electron‐Poor Olefins1. Issue 18 (5th March 2015) - Gicquel, Maxime; Zhang, Yang; Aillard, Paul; Retailleau, Pascal; Voituriez, Arnaud; Marinetti, Angela
Abstract The first use of phosphahelicene in enantioselective organocatalysis is reported. New chiral phosphahelicenes have been prepared and enable highly enantioselective [3+2] cyclization reactions between arylidene‐ or alkylidenemalononitriles and γ‐substituted allenoates or cyanoallenes. These reactions afford cyclopentene derivatives in both high yields and diastereoselectivities, with enantiomeric excesses of up to 97 %.